IMPLEMENTATINGTHE SANGGAU REGENCY REGIONAL REGULATION POLICY NO5 OF 2013 ONTHE IMPLEMENTATIONOF CHILD PROTECTION - YELSIE, DHENIE; Zulkarnaen, Zulkarnaen; Hutomo, Tri (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This study aims to describe the process of implementing the Sanggau Regency Regional Regulation Policy No. 5 of 2013 on the Implementation of Child Protection. This study used a qualitative research approach. The research location was in the Department of Social Affairs, Women's Empowerment, Child Protection and Family Planning of Sanggau Regency. The researcher used the theory of Jones, Charles O (Agustino, 2017:154) which explains three indicators of program implementation or policy implementation and there are three kinds of activities that need to be considered carefully. The three implementation indicators consist of: 1) Organization, it can be concluded that in order to facilitate the implementation of child protection policies and gather all OPDs in protecting and realizing children's rights and making Sanggau Regency a Child Friendly City; 2) Interpretation, it can be concluded that the Implementor at the Office of Social Affairs, Women's Empowerment, Child Protection and Family Planning has understood the objectives of the child protection policy well; 3) Application, the child protection policy program in Sanggau Regency can be concluded to be quite good and has received support from the community.